THE STUDENTS’ DECODING ABILITY IN COMPREHENDING READING A TEXT - setiawati, setiawati (STAI Hubbulwathan Duri, 2019)
This study aimed to know the students’ decoding ability in comprehending reading text. Related to the object of the research, the researcher used the descriptive method by using quantitative approach. The research was conducted at the fourth semester of English Program. The population of this research was the all students of fourth semester of English program at STAI Hubbulwathan Duri in academic year 2017/2018.The sample of the research was 13 students. In analyzing the research data, the researcher used SPSS. The data were taken from the students’ decoding ability in comprehending reading text is test score. Based on statistical calculation in data analysis, the researcher interpreted test score. From the calculation, the result mean values that researcher obtained through analyzing the data that has been collected from sixth components of decoding ability in comprehending reading text, they are previewing, reading for main idea, using context for vocabulary, scanning for detail, making inference and locating reference is around “76.73‖ and from that data, the researcher can conclude that the value is in ―Average‖ category.